Comparative effects of different types of cardioplegia in cardiac surgery: A network meta-analysis - Tan, Jia; Bi, Siwei; Li, Jingyi; Gu, Jun; Wang, Yishun; Xiong, Jiyue; Yu, Xiang; Du, Lei (Frontiers in Cardiovascular Medicine, 2022)
Objective: To compare the outcomes of four types of cardioplegia during cardiac surgery: del Nido (DN), blood cardioplegia (BC), histidine-tryptophan-ketoglutarate (HTK) and St. Thomas. Methods: Randomized controlled trials (RCTs) and observational cohort studies from 2005 to 2021 were identified in PubMed, Embase, and Cochrane databases. Data were extracted for the primary endpoint of perioperative mortality as well as the following secondary endpoints: atrial fibrillation, renal failure, stroke, use of an intra-aortic balloon pump, re-exploration, intensive care unit stay and hospital stay. A network meta-analysis comparing all four types of cardioplegia was performed, as well as direct meta-analysis comparing pairs of cardioplegia types. Results: Data were extracted from 18 RCTs and 49 observational cohort studies involving 18,191 adult patients (55 studies) and 1,634 children (12 studies). Among adult patients, risk of mortality was significantly higher for HTK (1.89, 95% CI 1.10, 3.52) and BC (RR 1.73, 95% CI 1.22, 2.79) than for DN. Risk of atrial fibrillation was significantly higher for BC (RR 1.41, 95% CI 1.09, 1.86) and DN (RR 1.51, 95% CI 1.15, 2.03) than for HTK. Among pediatric patients, no significant differences in endpoints were observed among the four types of cardioplegia. Conclusions: This network meta-analysis suggests that among adult patients undergoing cardiac surgery, DN may be associated with lower perioperative mortality than HTK or BC, while risk of atrial fibrillation may be lower with HTK than with BC or DN.